Capital inflows and direct foreign investment in Ireland 1952-1970 - McAleese, Dermot (Statistical and Social Inquiry Society of Ireland, 1972)
The role of foreign capital in activating and sustaining Ireland's post- War economic growth is a subject of compelling interest. The aims of this paper are twofold: first to examine the constituents of the capital inflow, paying particular regard to the experience of the last decade and, secondly, to analyse the composition, origin and principal features of direct investment in manufacturing enterprises.
Read before the Society, 28 January 1972
Keywords: Foreign direct investment; Capital inflows to Ireland; Irish industry; 314.15